The effect of light and temperature in the traditional “Wedang Uwuh” ready-to-drink (RTD) beverages on color stability and brazilin content during storage - Septiyani Retnosyari; Santoso Umar; Raharjo Sri; Wikandari Rachma (BIO Web of Conferences)
Wedang uwuh, a traditional drink from Yogyakarta, has potential as a functional beverage due to its antioxidant-rich ingredients like sappan wood, ginger, and cinnamon leaves. A key challenge in developing ready- to- drink (RTD) wedang uwuh is maintaining the red color, derived from brazilin in sappan wood, which also offers strong antioxidant benefits. This study aims to determine the effects of light and temperature on wedang uwuh ready to drink on color stability and brazilin content during storage. Samples consisted of control (C) which is a commercial wedang uwuh on the market without treatment and wedang uwuh treated with water blanching (1 minute, 85°C) and cabinet drying (12 hours, 55°C). The dried powder samples were then brewed at 85°C for 20 minutes, filtered and put in clear and brown glass bottles to store at room temperature to determine the effect of light. As for temperature, the samples were stored at room temperature (30°C), cold temperature (5°C) and Air Condition (AC) temperature (16°C). The results showed that light and temperature had an effect on color stability and brazilin content during 12-day storage. The a* value which shows the degree of red color in wedang uwuh RTD drinks during storage shows a greater decrease in clear bottles of 5.29 and 4.33 in control samples and samples with treatment than in brown bottles of 4.33 and 0.78 in control samples and samples with treatment. Brazilin content also decreased more in clear bottle storage. While at temperature storage, the best results were obtained at cold temperature storage (5°C) on color stability and brazilin content during 12 days storage.